Pengaruh Sarana Prasarana Kearsipan dan Penerapam Jadwal Retensi Arsip terhadap Penyusutan Arsip Inaktif di Dinas Ketahanan Pangan, Pertanian dan Perikanan Kota Bekasi - Supianah; Wahidin Septa Zahran (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This research is motivated by the phenomenon of inactive records accumulation, which leads to storage space congestion at the Department of Food Security, Agriculture, and Fisheries (DKPPP) of Bekasi City. This condition is triggered by limited physical facilities and suboptimal implementation of archival regulations as a basis for document destruction. The purpose of this study is to determine and analyze the influence of archival infrastructure and the implementation of Records Retention Schedules (RRS) on the effectiveness of inactive records disposal, both partially and simultaneously. The research method used is a quantitative method with an associative approach. The population in this study consists of all employees involved in records management within the DKPPP Bekasi City environment. Data collection techniques were carried out through questionnaires, observations, and documentation studies. Data analysis was performed using classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test and F-test). The results of the study indicate that: (1) Archival infrastructure has a positive and significant effect on the reduction of inactive archives, with a contribution of 25.7%; (2) The implementation of the Archive Retention Schedule (JRA) has a positive and significant effect on the reduction of inactive archives, with a contribution of 33.2%; (3) Simultaneously, archival infrastructure and the implementation of JRA have a significant effect on the success of the inactive archive reduction program, with a contribution of 58.9%. This indicates that the availability of adequate facilities and compliance with retention rules are the main keys in overcoming document accumulation.This indicates that the availability of adequate facilities and compliance with retention rules are key factors in addressing document accumulation. This study suggests that the institution should begin transforming towards archival digitalization through the implementation of e-files integrated with an automated RRS system. By leveraging information technology and strengthening the legality of digital documents, DKPPP Bekasi City can improve workspace efficiency and simplify the records disposal process without being constrained by physical infrastructure limitations in the future Keywords Archival Infrastructure, Records Retention Schedule (RRS), Records Disposal, Inactive Records, Digitalization